CURRENT TRENDS AND SPECIAL CHARACTERISTICS IN THE SPENDING OF THE EUROPEAN UNION’S REGIONAL DEVELOPMENT FUNDS - Szabo, Gabriella Gyorine (European Scientific Journal, ESJ, 2014)
The most important instruments of the EU’s regional development policy are the three funds made up of the GNI-pegged contributions of member states. The European Regional Development Fund, the European Social Fund and the Cohesion Fund – collectively the cohesion resources – fund all development aimed at facilitating the convergence process of the less developed regions within the EU and at retaining the competitiveness of the EU as a world region despite its being in the crossfire of internal and external challenges. This in turn means that the quantitative and qualitative considerations regarding how the funds spent are paramount. Nominal spending – that is the amount of the allocated funds actually accessed within the given 7+2-year timeframe – is measured by the absorption rate. However, "quality spending" i.e. efficient and effective usage of the resources is vital. The purpose of this study is to spotlight absorption: to determine the current access ratio of the overall 2007–2013 funding allocated a year and a half before the deadline. The author also focuses on spectacular differences in fund use in light of how the various member countries actually put them to work, together with the underlying reasons. The recently launched programme period of 2014–2020 is currently in its preliminary phase during which the EU members are working out their partnership agreements and operative programmes. The progression rates are different for each member state. For this timeframe the author explores the legislative background for a possible shift in allowed spending towards higher quality.